Pelatihan Penerapan Perhitungan Pajak Penghasilan Badan pada Koperasi bagi Peserta Praktik Lapang Perkoperasian di Daerah Istimewa Yogyakarta - Sugiyanto Sugiyanto (LPPM Universitas Koperasi Indonesia, 2023)
Every business entity or organization is certainly inseparable from the obligation to pay taxes as acontribution to the state. This also applies to cooperatives, cooperatives are taxpayers as well as taxcollectors. This training focused on the application of the calculation of corporate income tax. Thisactivity is carried out using an online training method supported by displaying visual material in theform of power points equipped with calculation examples in order to provide a clear and complete understanding of the application of corporate tax calculations in cooperatives. Then continued with questions and answers and discussions about the application of taxes on cooperatives. This training method can increase knowledge in applying taxes to cooperatives.